Factors related to the Incident Reporting Culture in Health Services: A Literature Review - Reni Astuti; Takdir Tahir; Kusrini S Kadar; Erfina Erfina (STRADA : Jurnal Ilmiah Kesehatan, 2021)
A literature search was performed using computerized databases of PubMed, ProQuest, Willey, and secondary searching journal portals. The keywords “patient safety, incidence report, and healthcare were used in various combinations. Inclusion criteria were as follows: written in the English language published in the last ten years and origin research, focusing on the cultural incident reporting, reported nurse staff, or other healthcare workers as participants. Exclusion criteria were: a review of literature or assessment tools development and report article. A total of 77 articles were obtained from the search. Of these, 70 articles were excluded due to did not meet the criteria of this review. We finally reviewed seven articles and categorized them into two main factors: Organizational culture and healthcare staff. This review emphasizes the importance of promoting the factors related to incidence reporting culture in health services, both organization level, and healthcare staff.